2023
DOI: 10.1021/acs.iecr.3c00706
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in CFD Simulations of Multiphase Flow Processes with Phase Change

Abstract: Phase change is a phenomenon that has been extensively utilized in chemical engineering, energy, electronics, vehicle, and space exploration. From both the science and engineering perspectives, gaining a profound understanding of the intricacies of multiphase flow processes accompanied by heat and mass transfer due to phase change is of fundamental importance. Indeed, the computational fluid dynamics (CFD) has been increasingly applied as an effective tool to give an in-depth and efficient analysis of the phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 444 publications
(786 reference statements)
0
6
0
Order By: Relevance
“…However, the Lee model was also not developed for a system with such a wide temperature variation, and presumably more advanced models , should be employed for a better match of the pressure. Given that the current results are reasonably close to the experimental values and that an exact match of the gas phase pressure is usually superfluous when simulating hydrothermal reactors, the standard form of the Lee model may be a good choice due to its robustness and limited computational burden . Some more comments on these observations are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…However, the Lee model was also not developed for a system with such a wide temperature variation, and presumably more advanced models , should be employed for a better match of the pressure. Given that the current results are reasonably close to the experimental values and that an exact match of the gas phase pressure is usually superfluous when simulating hydrothermal reactors, the standard form of the Lee model may be a good choice due to its robustness and limited computational burden . Some more comments on these observations are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 52%
“…Previous research has shown that this model has some shortcomings, such as the neglect of the superheat needed to activate nucleation sites in the liquid, and more complex alternatives have been proposed . Nonetheless, the model is widely employed in the literature, and here it was selected as a reasonable compromise. For the coefficients γ l and γ v , the Fluent guide recommends tuning their values to match the experimental results, while Sun et al .…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Here, the previously mentioned dynamic contact angle models play a vital role. , Another exciting research area that needs intense future research is the modeling and incorporation of contact angle hysteresis . Followed by this, numerical modeling of phase change heat transfer processes is an ongoing research topic . Lastly, using machine learning to identify flow fields and flow structures in complex multiphase flow scenarios is also gaining popularity. , …”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…However, HTC also involves other phenomena that are usually not relevant for other systems. One of these is evaporation and other phase transfers [4]: their inclusion is mandatory to assess the gas pressure and yield, but such models clearly complicate the setup [69]. Furthermore, the evaporation models commonly applied in the literature were not originally designed for systems with such substantial temperature variations.…”
Section: Cfd Modelsmentioning
confidence: 99%